The Impact of Outliers and Leverage Points for Technical Efficiency Measurement Using High Breakdown Procedures - Seaver, Bill L.; Triantis, Konstantinos P. (Management Science, 1995)
Given that most data used for production studies have not been accumulated for such purposes, it is important that the quantitative tools for messy data which can affect the accuracy of computed technical efficiency measures be found. In this study, high breakdown robust methods are used in conjunction with a robust distance measure defined relative to the minimum volume ellipsoid estimator. The standardized robust residuals from the high breakdown estimators and the robust distance measures are used to statistically and graphically depict both multivariate outliers and leverage points. Once these points are found, their relationship to those observations that exhibit strong technically efficient or inefficient behavior, scale inefficiency and/or unusual production characteristics is analyzed for three linerboard manufacturing facilities. Additionally, the impact of the outliers and leverage points on the estimated least squares coefficients which are used by the corrected ordinary least squares methodology to compute the full-frontier technical efficiency measures is explored. Finally, a sensitivity analysis of the impact of outliers and leverage points on the computed linear programming based technical efficiency measures is presented.